2019
DOI: 10.5222/head.2019.125
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Level of Social Support among Pregnant Women and Affecting Factors

Abstract: Amaç: Çalışma, gebelerin algılanan sosyal destek düzeyi ve etkileyen faktörleri belirlemek amacıyla yapılmıştır. Yöntem: Tanımlayıcı tipte olan araştırmada örneklemi zihinsel engeli olmayan, okuma-yazma bilen, gebelikle ilgili herhangi bir riski bulunmayan 329 gebe oluşturmuştur. Araştırma öncesinde ilgili kurum ve kişilerden etik izinler alınmıştır. Veriler Sağlık Bakanlığı Risk Değerlendirme Formu, Gebe Tanılama Formu, Çok Boyutlu Algılanan Sosyal Destek Ölçeği (ÇBASDÖ) ile gebelerle yüz yüze görüşülerek top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The mean MSPSS score of the pregnant women who participated in the study was determined as 69.56 ± 14.34. Studies examining pregnant women’s MSPSS reported values as 53.86 ± 20.21 (28), 55.34 ± 15.96 (29), 66.7 ± 14.1 (30), 66.70 ± 15.54 (31) and 60.87 ± 13.04 (32). The mean MSPSS score in our study was similar to those reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean MSPSS score of the pregnant women who participated in the study was determined as 69.56 ± 14.34. Studies examining pregnant women’s MSPSS reported values as 53.86 ± 20.21 (28), 55.34 ± 15.96 (29), 66.7 ± 14.1 (30), 66.70 ± 15.54 (31) and 60.87 ± 13.04 (32). The mean MSPSS score in our study was similar to those reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Awareness about the importance of psychosocial health problems and insufficiency of social support which may adversely affect the health of the mother and the baby during pregnancy and the postpartum period is increasing. However, routine evaluation of these problems during prenatal care is quite limited (28, 21). Therefore, this study investigated the relationship between women's perceptions of traumatic childbirth and provided psychosocial health and social support.…”
Section: Discussionmentioning
confidence: 99%